2021
DOI: 10.1155/2021/8854915
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Novel Herbal Formulation (F2) on the Management of Obesity: In Vitro and In Vivo Study

Abstract: Background. Currently, obesity and its comorbidities have become a serious threat to human health necessitating urgent development of safe and effective therapy for their management. Materials and Methods. In this research, a novel polyherbal formulation (F2) was prepared by mixing specific proportions of royal jelly and lemon juice with ethanol extracts of Orostachys japonicus, Rhus verniciflua, and Geranium thunbergii. The antioxidant activity was assessed using DPPH and ABTS assay methods. The antiobesity p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 61 publications
3
19
1
Order By: Relevance
“…Herbs that have shown good anti-adipogenic activity in scientific evaluation are Piper nigrum [44], Camellia sinensis [45], Trigonella foenum-graecum [46], Zingiber officinale [47], Aegle marmelos [48], Sibiraea augustata [49] and Corni Fructus [50], etc. Formulations obtained from herbal mixtures, such as Triphala [51], Vrikshamla [52], Dohongsamul-tang [53], Samchulgeonbi-tang [54], SH21B [55], Oyaksungi-san [56] and formulation F2 [57], etc. have also proven their efficacy for both the treatment of obesity and anti-adipogenic potential in in-vitro and in-vivo experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Herbs that have shown good anti-adipogenic activity in scientific evaluation are Piper nigrum [44], Camellia sinensis [45], Trigonella foenum-graecum [46], Zingiber officinale [47], Aegle marmelos [48], Sibiraea augustata [49] and Corni Fructus [50], etc. Formulations obtained from herbal mixtures, such as Triphala [51], Vrikshamla [52], Dohongsamul-tang [53], Samchulgeonbi-tang [54], SH21B [55], Oyaksungi-san [56] and formulation F2 [57], etc. have also proven their efficacy for both the treatment of obesity and anti-adipogenic potential in in-vitro and in-vivo experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Upon administration of BSE, a decrease in weight gain and a decrease in FER (food efficiency ratio) were observed in a dose-dependent manner. FER is the ratio of increasing weight to food intake, and a decrease in FER means less weight gain compared to food intake [ 61 , 62 , 63 , 64 ]. As adipose tissue weight reduction, adipocyte growth inhibition through morphology, and differentiation inhibition through Western blotting were observed, it was confirmed that the anti-obesity effect of BSE was a factor in reducing FER.…”
Section: Discussionmentioning
confidence: 99%
“…Adipocyte differentiation and measurement of lipid accumulation were done according to the method described in the previous study with slight modification (Pandeya et al, 2021). The 3T3-L1 pre-adipocytes were seeded at a density of 5.2 × 10 3 cells/well of 24 well-plates and 6 × 10 4 cells/well of 6 well plates in DMEM supplemented with 10% NCS media.…”
Section: Cell Culture and Adipocyte Differentiationmentioning
confidence: 99%
“…The epididymal white adipose tissue, liver, kidney, and spleen were isolated, weighed, and immediately fixed into 10% formalin with PBS for histological analysis. Hematoxylin and eosin (H&E) staining was done for histological analysis according to the method described in the previous report (Pandeya et al, 2021). Micrographs were analyzed using an EVOS XL core light microscope.…”
Section: Histological Analysismentioning
confidence: 99%